2001
DOI: 10.1111/j.1745-4565.2001.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

HEAT RESISTANCE OF CLOSTRIDIUM PERFRINGENS VEGETATIVE CELLS AS AFFECTED BY PRIOR HEAT SHOCK1

Abstract: This study quantified the heat resistance and the effects of a heat shock on the subsequent heat resistance of 10 strains of Clostridium perfringens. Beef gravy samples inoculated with vegetative cells of the pathogen were subjected to sublethal heating at 48C for 10 min, and then heated to a final temperature of 58C using a submerged‐coil heating apparatus. Heat‐treated samples were spiral plated on Shahidi‐Ferguson Perfringens agar to determine surviving bacterial population. No correlation between the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…perfringens vegetative cells will be inactivated at temperatures around 60°C (Juneja et al, 2001), but even foods cooked to proper temperatures can harbor C. perfringens spores. Ideal conditions for complete spore inactivation are less well defined (Akhtar et al, 2009), and include a combination of temperature and pressure.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…perfringens vegetative cells will be inactivated at temperatures around 60°C (Juneja et al, 2001), but even foods cooked to proper temperatures can harbor C. perfringens spores. Ideal conditions for complete spore inactivation are less well defined (Akhtar et al, 2009), and include a combination of temperature and pressure.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Asselt e Zwietering (2006) apresentaram valor médio de 10,3ºC procedente de outros cinco trabalhos (ROY et al, 1981;ICMSF, 1996;MARMER, 1998;JUNEJA et al, 2001;NOVAK et al, 2001). Valor Z é dependente de parâmetros obtidos nas curvas de destruição térmica estando, assim, também sob a influência dos mesmos fatores, estudados por outros autores, que sabidamente afetam as determinações destas referidas curvas.…”
Section: Tratamentos Térmicos Curvas De Destruição Térmicaunclassified
“…Valor Z é dependente de parâmetros obtidos nas curvas de destruição térmica estando, assim, também sob a influência dos mesmos fatores, estudados por outros autores, que sabidamente afetam as determinações destas referidas curvas. Fenômeno protetivo de células bacterianas atribuído a componentes alimentares de substratos (matrizes) experimentados são comumente encontrados e/ou mencionados por autores (e. g. JUNEJA; MARMER, 1998;JUNEJA et al, 2001;WIJNANDS et al, 2009) e possivelmente podem ter influenciado os padrões díspares aqui explicitados. Figura 2 -Relação entre os tempos de redução decimal (observados e calculados) obtidos a partir de tratamentos térmicos de células vegetativas do Clostridium perfringens em patê de fígado com nozes e passas e do modelo preditivo utilizado.…”
Section: Tratamentos Térmicos Curvas De Destruição Térmicaunclassified
See 1 more Smart Citation
“…However, little information is available regarding inactivation of vegetative cells under heat-shock conditions. To date, several studies on the heat resistance of vegetative cells have been carried out with C. perfringens (19,23,24). On the other hand, little study has been found in literature on the heat resistance of C. sporogenes vegetative cells.…”
Section: )mentioning
confidence: 99%